Nutritional therapy for burns in children - Galfo, Myriam; De Bellis, Andrea; Melini, Francesca (Journal of Emergency and Critical Care Medicine; Vol 2 (June 2018): Journal of Emergency and Critical Care Medicine, 2018)
Among children, burns are a serious injury and one of the main reasons of trauma, especially during the first 5 years of life. For these patients, the nutritional support has been acknowledged as one of the most significant aspect of the medical burns treatment in terms of mere nutrition, because of a marked hypermetabolism immediately or early after burn and protection from infections. Resting energy expenditure (REE) has a curvilinear increasing trend according to the total burned surface area (TBSA), and indirect calorimetry is considered the most accurate method to evaluate the energy output of burned patients. Protein need in burned children is generally agreed to be higher than recommended dietary allowance and intake thereof should range around 1.5–3.0 g/kg/die. Carbohydrate intake should be 55–60% of total energy intake (TEI), whereas lipids should be lower than 35% of TEI. As regards micronutrients intake, children suffering from major burns should receive vitamin supplementation in the form of a multivitamin, in addition to vitamin C, vitamin A and zinc sulfate to ensure adequate wound healing. Enteral nutrition is the first line of nutritional support in the burned patient, and enteral feeding should be administered as soon as possible. When enteral nutrition is contraindicated or not feasible, parenteral nutrition is used.